Odontanthias randalli n. sp., a new anthiine fish (Serranidae: Anthiinae) from Indonesia WILLIAM T. WHITE (Australia) - White, William T. (Zootaxa, 2011)
Odontanthias randalli, a new species of anthiine serranid fish from southeastern Indonesia, is described, bringing the number of known species in the genus to 14. The new species is clearly distinguished from other members of the genus by the following combination of characters: dorsal-fin soft rays 16–17, lateral-line scales 37 to 39, 3rd dorsal spine longest, 3rd dorsal-fin soft ray the only filamentous dorsal-fin ray, caudal fin lunate with extremely long filamentous lobes, depth of body 2.2 to 2. 5 in SL, vomerine-tooth patch arrowhead shaped, and body pinkish with bright yellow spots on upper half and four pale pink blotches below dorsal-fin base. The new species is compared with other members of the genus.